Correlating dynamic characteristics from field measurements and numerical analysis of a high rise building. - Brownjohn, J.M.W (Earthquake engineering & structural dynamics.)
Using the concept of lumped masses and rigid floor slabs, several mathematical models were built using a popular PC-based finite element program to model a tall building with a frame core wall structural system. These models were analysed to obtain the first nine mode shapes and their natural frequencies which were compared with those from field measurements, using numerical correlation indicators. The comparison shows several factors that can have a significant effect on the analysis results. Firstly, outriggers connecting the outer framed tube ystem to the inner core walled tube system have a significant effect on fundamental translational mode behaviour. Secondly, detailed modelling of the core considering major and minor openings as well as internal thin walls has the strongest influence on torsional behaviour, whose measurements were shown to be an important aspect of the dynamic behaviour for the structure studied. Fine tuning of an analytical model requires not just considering variation in values of structural parameters but also attention to fine detail.